AN ESP NEEDS ANALYSIS IN BUSINESS ENGLISH - Cahyaningrum, Tri; Arroyyani, Risa (Journal of Innovation Research and Knowledge, 2024)
Business students are required to be proficient in English due to the business communication needs that demand English language skills. With this requirement, there is a need for English language learning materials, as part of ESP, which meets the students’ needs. This research aims to conduct a needs analysis for Business students to identify their needs, lacks, and wants related to English classes. The findings indicate that their objectives of learning English are for academic purposes as well as future professional preparation. They face challenges in learning English, particularly in public speaking. The desired English language learning experience for them is one that is enjoyable, fun, utilizes various media, and involves active teacher participation to help them understand business English learning materials.